Investigation of power converters for AC and DC power collection in wind turbine systems - Khan, Md Shafquat Ullah (Nanyang Technological University, 2020)
Wind turbine systems (WTSs) have become one of the significant contributors to renewable energy and pledges the formidable reduction of global dependence on fossil fuel. With the overall increase in wind power production, individual wind turbines are also getting bigger producing power rating as high as 20 MW. WTSs are a complex electro-mechanical system, and as the wind turbines are getting bigger, vibration issues are becoming one of the concerning issues. Torsional vibration is one of the dominant contributors of failures pertinent to mechanical aspects which statistically causes the highest downtime to the WTS. Though the electrical system has lower downtime than the mechanical system, the power electronic components in the system add to the highest annual failure rate. As the installation of WTS is on a high in offshore scenarios, the reliability, and failure contingencies become one of the major concerns for the utilities. The research world is continuously striving for solutions in this regards for high power applications. Wind dynamics and grid side disturbances affecting the stability of the system required further analysis more than ever before.